A survey about impacts of cloud computing on digital forensics - Daryabar, Farid; Dehghantanha, Ali; Udzir, Nur Izura; Mohd Sani, Nor Fazlida; Shamsuddin, Solahuddin; Norouzizadeh, Farhood (The Society of Digital Information and Wireless Communications, 2013)
Nowadays, digital storage of computer data is moving toward cloud computing which is a set of infrastructure provides data storage for organizations and individuals. Due to this large scale, in case an attack occurs in the network of a cloud it would be a big challenge to investigate the cloud. Therefore, digital forensics in cloud computing is a new discipline related to the increasing use of computers, networks and digital storage devices in numerous criminal activities in both traditional and Hi-Tech. This study reviews the literature on some challenges in cloud computing forensic investigation, and it is followed by evaluation and analysis of all types of information on cloud computing and its impacts on computer forensic investigations in publishing alliances with the survey was carried out in the field.